Temperature dependence of interfacial properties and viscosity of nanofluids for droplet-based microfluidics - Murshed, S. M. Sohel (2012)
Interfacial tension and viscosity of a liquid play an important role in microfluidic systems. In this study, temperature dependence of surface tension, interfacial tension and viscosity of a nanofluid are investigated for its applicability in droplet-based microfluidics. Experimental results show that nanofluids having TiO2 nanoparticles of 15 nm diameter in deionized water exhibit substantially smaller surface tension and oil-based interfacial tension than those of the base fluid (i.e. deionized water). These surface and interfacial tensions of this nanofluid were found to decrease almost linearly with increasing temperature. The Brownian motion of nanoparticles in the base fluid was identified as a possible mechanism for reduced surface and interfacial tensions of the nanofluid. The measured effective viscosity of the nanofluid was found to be insignificantly higher than that of the base fluid and to decrease with increasing fluid temperature. The dependence on the temperature of the droplet formation at the T-junction of a microfluidic device is also studied and the nanofluid shows larger droplet size compared with its base fluid.